Sodium and water intake are not affected by GABAC receptor activation in the lateral parabrachial nucleus of sodium-depleted rats - Domingos-Souza, Gean (2016)
The activation of GABAergic receptors, GABAA and GABAB, in the lateral parabrachial nucleus (LPBN) increases water and sodium intake in satiated and fluid-depleted rats. The present study investigated the presence of the GABAC receptor in the LPBN, its involvement in water and sodium intake, and its effects on cardiovascular parameters during the acute fluid depletion induced by furosemide combined with captopril (Furo/Cap). One group of male Wistar rats (290-300 g) with bilateral stainless steel LPBN cannulas was used to test the effects of a GABAC receptor agonist and antagonist on the fluid intake and cardiovascular parameters. We investigated the effects of bilateral LPBN injections of trans-4-aminocrotonic acid (TACA) on the intake of water and 0.3 M NaCl induced by acute fluid depletion (subcutaneous injection of Furo/Cap). c-Fos expression increased (P<0.05), suggesting LPBN neuronal activation. The injection of different doses of TACA (0.5, 2.0 and 160 nmol) in the LPBN did not change the sodium or water intake in Furo/Cap-treated rats (P > 0.05). Treatment with the GABAC receptor antagonist (Z)-3-[(aminoiminomethyl)thio]prop-2-enoic acid sulfate (ZAPA, 10 nmol) or with ZAPA (10 nmol) plus TACA (160 nmol) did not change the sodium or water intake compared with that for vehicle (saline) (P > 0.05). Bilateral injections of the GABAC agonist in the LPBN of Furo/Cap-treated rats did not affect the mean arterial pressure (MAP) or heart rate (HR). The GABAC receptor expression in the LPBN was confirmed by the presence of a 50 kDa band. Although LPBN neurons might express GABAC receptors, their activation produced no change in water and sodium intake or in the cardiovascular parameters in the acute fluid depletion rats. Therefore, the GABAC receptors in the LPBN might not interfere with fluid and blood pressure regulation.